2015
DOI: 10.1016/j.juro.2015.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Nadir Testosterone after Long-Term Followup Predicts Prognosis in Patients with Prostate Cancer Treated with Combined Androgen Blockade

Abstract: Nadir testosterone 20 ng/dl was the most significant cutoff level for overall survival in Japanese patients with prostate cancer treated with combined androgen blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 19 publications
0
36
1
2
Order By: Relevance
“…31 A multicentre study analyzed data from 225 patients receiving complete androgen blockade with an LHRH agonist or antagonist, or surgical castration plus antiandrogens for localized, locally advanced, or metastatic PCa. 26 The data demonstrated improved outcomes for patients with testosterone levels <0.7 nmol/l compared with those with testosterone ≥0.7 nmol/l. Median PFS was 16.3 vs. 11.0 months (p=0.1163), while median OS was 68.3 vs. 28.3 months (p<0.0014), respectively.…”
Section: Retrospective Datamentioning
confidence: 85%
See 4 more Smart Citations
“…31 A multicentre study analyzed data from 225 patients receiving complete androgen blockade with an LHRH agonist or antagonist, or surgical castration plus antiandrogens for localized, locally advanced, or metastatic PCa. 26 The data demonstrated improved outcomes for patients with testosterone levels <0.7 nmol/l compared with those with testosterone ≥0.7 nmol/l. Median PFS was 16.3 vs. 11.0 months (p=0.1163), while median OS was 68.3 vs. 28.3 months (p<0.0014), respectively.…”
Section: Retrospective Datamentioning
confidence: 85%
“…[21][22][23]27,29 Four of six retrospective studies of localized, locally advanced, or metastatic PCa also demonstrated improved outcomes (lower rates of testosterone breakthrough, PFS, CSS, or OS) for patients achieving testosterone suppression ≤0.7 nmol/l or ≤1.1 nmol/l compared to those with serum testosterone levels >0.7 nmol/l or >1.1 nmol/l, respectively. 26,28,30,31 A similar trend was seen in a recent post-hoc analysis of the ICELAND study, which demonstrated an association between lower nadir testosterone level and a trend toward longer time to PSA (CRPC) progression (≤0.7 nmol/l vs. >0.7 nmol/l to ≤1.7 nmol/l; HR 5.06; 95% CI 1.3-16.1; p=0.062; at the time of publication, the ICELAND study report was only available in abstract form). 32 Overall, these data provide compelling support for a relationship between low testosterone levels and improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations